Ice melting and downward transport of meltwater by two‐phase flow in Europa's ice shell. Issue 3 (11th March 2014) - Kalousová, Klára; Souček, Ondřej; Tobie, Gabriel; Choblet, Gaël; Čadek, Ondřej
<x xml:space="preserve">Abstract</x> With its young surface, very few impact craters, and the abundance of tectonic and cryovolcanic features, Europa has likely been subjected to relatively recent endogenic activity. Morphological analyses of chaos terrains and double ridges suggest the presence of liquid water within the ice shell a few kilometers below the surface, which may result from enhanced tidal heating. A major issue concerns the thermal/gravitational stability of these water reservoirs. Here we investigate the conditions under which water can be generated and transported through Europa's ice shell. We address particularly the downward two‐phase flow by solving the equations for a two‐phase mixture of water ice and liquid water in one‐dimensional geometry. In the case of purely temperate ice, we show that water is transported downward very efficiently in the form of successive porosity waves. The time needed to transport the water from the subsurface region to the underlying ocean varies between ∼1 and 100 kyr, depending mostly on the ice permeability. We further show that water produced in the head of tidally heated hot plumes never accumulates at shallow depths and is rapidly extracted from the ice shell (within less than a few hundred kiloyears). Our calculations indicate that liquid water will be largely absent in the near subsurface, with the possible exception of cold conductive regions subjected to strong tidal friction. Recently active double ridges subjected to large tidally driven strike‐slip motions are perhaps the most likely candidates for the detection of transient water lenses at shallow depths on Europa.